Brown and Beige Adipose Tissue and Aging - Zoico, Elena; Rubele, Sofia; De Caro, Annamaria; Nori, Nicole; Mazzali, Gloria; Fantin, Francesco; Rossi, Andrea; Zamboni, Mauro (Frontiers in Endocrinology, 2019)
Across aging, adipose tissue (AT) changes its quantity and distribution: AT becomes dysfunctional with an increase in production of inflammatory peptides, a decline of those with anti-inflammatory activity and infiltration of macrophages. Adipose organ dysfunction may lead to age-related metabolic alterations. Aging is characterized by an increase in adiposity and a decline in brown adipose tissue (BAT) depots and activity, and UCP1 expression. There are many possible links to age-associated involution of BAT, including the loss of mitochondrial function, impairment of the sympathetic nervous system, age-induced alteration of brown adipogenic stem/progenitor cell function and changes in endocrine signals. Aging is also associated with a reduction in beige adipocyte formation. Beige adipocytes are known to differentiate from a sub-population of progenitors resident in white adipose tissue (WAT); a defective ability of progenitor cells to proliferate and differentiate has been hypothesized with aging. The loss of beige adipocytes with age may be caused by changes in trophic factors in the adipose tissue microenvironment, which regulate progenitor cell proliferation and differentiation. This review focuses on possible mechanisms involved in the reduction of BAT and beige activity with aging, along with possible targets for age-related metabolic disease therapy.